Regional integration and trade: The case of the common market for Eastern and Southern Africa (COMESA) Free Trade Area - Grace Gondwe (Journal of African Trade, 2021)
This paper examines the factors influencing intra-Common Market for Eastern and Southern Africa (COMESA) trade by empirically investigating whether the Free Trade Area (FTA) contributed to trade growth from 1997 to 2015. Gravity models for exports and imports were estimated to identify the factors influencing intra-COMESA trade. The results show that the FTA has bolstered trade in the region. The results further reveal that the presence of other regional blocs, such as the Southern African Development Community and the European Union, positively influences trade in the region. Positive and significant Linder coefficients were found in both models, indicating that similar underlying factors currently influence the direction of exports and imports. Based on comparative advantages, countries export commodities with little or no value addition. They import differentiated goods, however, consisting mainly of processed materials of the products that they initially exported. Thus, the COMESA FTA benefits are not fully exploited and that export diversification and the development of viable value chains within and among its member countries would appear to be the best policy options. Lastly, the results indicate positive returns to better economic infrastructure. Specifically, the positive and significant coefficient of the transport variable for both exports and imports highlights the importance of good transport infrastructure for enhanced trade in the region. With increased distance, however, the results suggest that information and communications technology in the reporting country is effective at enhancing exports. As such, prioritising investments in transport and information and communications infrastructure is important for COMESA to improve its export performance.
Keywords: 330; COMESA; free trade area; trade; regional integration; gravity